Injury surveillance at a level 1 trauma centre in Johannesburg, South Africa - Judith C Bruce; Shelley Schmollgruber; Jocelyn Eales; Jasmin Gassiep; Vanessa Doubell (AOSIS, 2003)
An analysis of 16 357 trauma patients seen over a one year period at the trauma casualty of an academic hospital in Johannesburg was carried out to determine the profile of injuries sustained by victims in the Johannesburg region. Opsomming 'n Analise van 16 357 trauma-pasiënte gesien in 'n een-jaar periode in die trauma-ongevalle van 'n akademiese hospitaal in Johannesburg, is uitgevoer ten einde 'n profiel van beserings wat opgedoen is deur slagoffers, in die Johannesburg-area, te bepaal. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.